Characteristics Analysis of Sludge from a Leachate Treatment Plant for Sustainable Construction Material - Ayu Wulandari, Anindya Hesty; Chaerul, Mochammad (ITB Graduate School Conference, 2025)
Rapid population growth and increasingly complex community activities have a direct impact on the increase in waste. For this reason, a Final Disposal Site (FDS) is needed. The increase in waste volume at the LTP generates leachate containing organic and inorganic pollutants, as well as heavy metals. To mitigate environmental impacts, the leachate is treated through a Leachate Treatment Plant (LTP), which produces sludge as one of the residues from the treatment process. This sludge has the potential to become hazardous waste if not managed properly. This study aims to analyze the physical and chemical characteristics of the sludge produced by the LTP, as well as evaluate its potential for utilization. The results show that the sludge has a fineness modulus of 2.32, which falls within the range for fine aggregates according to ASTM C33. But, metal oxide content does not meet the criteria for pozzolanic material. Therefore, LTP sludge is not suitable as a cement substitute. However, it has potential as a partial substitute for sand in most structural concrete materials and requires cement as a binder. Sludge can reducing environmental pollution.